Analysis of The Implementation of Pharmaceutical Service Standards in Accordance with The Minister of Health Regulation 73 of 2016 on The Management of Preparations in Pharmacies in Jepara Regency - Lu’lu’atul Miskiyah; Ria Etikasari; Ahmad Suriyadi Muslim (Advances in Healthcare Research, 2026)
Purpose: This study aimed to analyze the level of implementation of Pharmaceutical Service Standards in accordance with the Minister of Health Regulation No. 73 of 2016 in the management of pharmaceutical preparations in pharmacies in Jepara Regency and to identify supporting factors and obstacles in its implementation. Research Method: This study employed a descriptive, quantitative design with an observational, cross-sectional approach. The population consisted of 218 active pharmacies in Jepara Regency, and a minimum sample of 69 pharmacies was selected using purposive sampling. Data were collected through questionnaires, observations, and documentation, focusing on planning, procurement, receiving, storage, control, destruction, and recording and reporting. Data were analyzed univariately using frequencies, percentages, and averages. Results and Discussion: The implementation of pharmaceutical preparation management was generally in accordance with the standard. Most pharmacies showed high compliance across planning, procurement, receiving, storage, destruction, and recording and reporting. However, several aspects still require improvement, particularly the use of disease-pattern data in planning, pharmacist supervision during procurement, consistency of stock card recording, and the completeness of documentation and reporting. Implications: These findings indicate that pharmaceutical service standards have been widely implemented, but ongoing supervision, training, and system strengthening are needed to ensure more consistent and sustainable compliance across all pharmacies.